Enhancing strength and ductility of AlSi10Mg fabricated by selective laser melting by TiB2 nanoparticles. (20th May 2022) - Xiao, Y.K.; Chen, H.; Bian, Z.Y.; Sun, T.T.; Ding, H.; Yang, Q.; Wu, Y.; Lian, Q.; Chen, Z.; Wang, H.W.
Highlights: Introduced nano-TiB2 achieves CTE transition, grain refinement and texture elimination. The strength and ductility are improved simultaneously by the nano-TiB2 particles. The influence mechanisms of the nanoparticles on ductility are clarified. Abstract: In the metallic components fabricated by the emerging selective laser melting (SLM) technology, most strategies used for strengthening the materials sacrifice the ductility, leading to the so-called strength-ductility trade-off. In the present study, we report that the strength and ductility of materials can be enhanced simultaneously by introducing nanoparticles, which can break the trade-off of the metallic materials. In the case of in-situ nano-TiB2 decorated AlSi10Mg composites, the introduced nanoparticles lead to columnar-to-equiaxed transition, grain refinement and texture elimination. With increasing content of nanoparticles, the strength increases continually. Significantly, the ductility first increases and then decreases. Our results show that the ductility is controlled by the competition between the crack-induced catastrophic fracture and ductile fracture associated with dislocation activities. The first increase of ductility is mainly attributed to the suppression of crack-induced catastrophic fracture when TiB2 nanoparticles present. With the further increase of TiB2 nanoparticles, the subsequent decrease of ductility is mainly controlled by dislocation activities. Thus, the materials will exhibit the optimum strength and ductility combination in a certain range of TiB2 nanoparticles. This study clarifies the physical mechanism controlling ductility for nano-TiB2 decorated AlSi10Mg composites, which provides the insights for the design of structural materials. Graphical abstracts: Image, graphical abstract